(NkURS sOL_FEDVIO(B.(NdIATONIKA(B.s (NU^EBNOE POSOBIE(B, (NNOTYs - (Na(B.(Np(B.(NaGAVANOW(B.s ((NsANKT(B-(NpETERBURGs (NlAN_s (NpLANETA mUZYKIs, 2020)
(NsOL_FEDVIO(B- (NWAVNEJ[AQ DISCIPLINA MUZYKAL_NOGO OBROZOWANIQ(B,(NNARQDU S \LEMENTARNOJ TEORIEJ MUZYKI(B,(NGARMONIEJ(B0(NANALIZOM MUZYKALNYH PROIZWEDENIJ(B.s
(N|TA NOWAQ KNIGA(B.s
Keywords: (NsOL_FEDVIOs